PROPOSALS FOR IMPROVING THE MECHANISM FOR IMPLEMENTING THE REGIONAL FOOD MARKET INTO PRACTICAL MEASURES (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The article reveals the domestic potential of food production. A set of measures to be implemented in the Fergana region to achieve the strategic indicators of agricultural development of the Republic of Uzbekistan for 2020-2030 has been developed. Scientific proposals and practical recommendations aimed at improving the regional food market are given.